Kieli ja eläin Vuorovaikutusta ja kielioppia monilajisissa yhteisöissä - Peltola, Rea; Jääskeläinen, Anni; Harjunpää, Katariina (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
This collection of articles sheds light on the role of human language in interspecies interaction. The book shows that language is not necessarily what separates us from other creatures. It can also be seen as yet another dimension of human existence that is deeply rooted in our shared history and everyday life with other living beings. This volume contains six individual research articles, two short reviews, an opening introduction to the themes of the book, and an extensive, theoretical closing chapter. The studies draw on methodologies and theoretical approaches including conversation analysis and a cognitive, usage-based approach to grammatical constructions. The book further explores the interfaces of linguistics, biosemiotics, and posthumanism. The studies show how linguistic and interactional approaches can contribute to our understanding of how human and non-human animals communicate with each other during embodied activities, how human language users make sense of interspecies encounters in speaking to or about animals, and how human language is thereby impregnated by the presence of other species. The individual research articles study, e.g., interaction with co-present animals, dialectal cow calls, parliamentary speeches, narratives of nature observation, and historical laws.